Surgical infrainguinal revascularization for peripheral arterial disease: factors affecting patency rate - Jafarian, Ali (Med J Islam Repub Iran, 2015)
Background: Peripheral arterial disease is a source of morbidity and mortality. Surgical vascular reconstruction is a treatment option but probability of failure and complications are important concerns. In this study, we evaluated outcome of surgical infrainguinal reconstruction and factors affecting graft patency for a period of one year. Methods: In this cohort study, 85 consecutive patients with chronic ischemia who underwent lower extremity surgical vascular reconstruction (including 52 femoropopliteal and 25 femorofemoral bypass) from March 2007 to Feb 2009 were recruited. Graft patency was evaluated before discharge from hospital and one year after the surgical operation using duplex ultrasonography. Association between possible risk factors and graft patency were evaluated. Results: In general, 71% (37 patients) of femoropopliteal and 52% (13 patients) of femorofemoral reconstructions were patent during the follow up period. Diabetes mellitus, hypertension, smoking, opium use and ischemic heart disease were significantly associated with decreased rate of patency (p<0.05). Conclusion: Assessing risk factors that predict perioperative mortality and graft patency is essential for selecting patients that would benefit from surgery. Omitting surgical reconstruction and endovascular intervention may be preferable especially when multiple risk factors are present or in the absence of critical limb ischemia.